Analysis of Student Mentality with Rating Scale Mental Effort on Online Lecturing - Mira Rahayu; Dino Caesaron; Celline Isabel Elvira Angkuw; Helena Dinda; Muhammad Khalid Asyafi'i; Muhammad Rifqi Fahmi (School of Industrial and System Engineering, Telkom University, 2022)
Online lectures are distance learning carried out by all students and teachers who are in separate locations and involve multiple platforms in the implementation of online lectures. The problems experienced by students related to online lectures such as difficulties in using technology, and understanding the material so that it triggers a high mental workload from each student. This study aims to analyze the mental workload of industrial engineering students at Telkom University, Bandung. This study uses the Rating Scale Mental Effort (RSME) method to determine the mental workload related to the use of technology in online lectures. In the results of measuring mental workload, using a questionnaire distributed to students with 48 respondents. Based on the results obtained, the indicator that received the highest average RSME value reached 83.75, on the work anxiety indicator. Therefore, it is necessary to improve online learning and further research.